2019
DOI: 10.4269/ajtmh.19-0392
|View full text |Cite
|
Sign up to set email alerts
|

Severe Fever with Thrombocytopenia Syndrome Virus Infection or Mixed Infection with Scrub Typhus in South Korea in 2000–2003

Abstract: Severe fever with thrombocytopenia syndrome is a tick-borne viral disease, with a high mortality rate that was first reported in China in 2009. Scrub typhus is an acute febrile illness caused by Orientia tsutsugamushi, a bacterium transmitted to humans through chigger mite bites. Severe fever with thrombocytopenia syndrome and scrub typhus are endemic to South Korea. To investigate evidence of severe fever with thrombocytopenia syndrome virus (SFTSV) infection or mixed infection with scrub typhus in South Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…SFTSV infections are endemic in eastern Asia, and retrospective studies have confirmed its presence in China in 1996 (6), South Korea in 2000 7, Japan in 2005 (8), and Vietnam in 2017 (9). In addition, mixed infection with SFTSV and O. tsutsugamushi has been detected in patients in South Korea, where both pathogens are endemic (7,10). These results further emphasize the urgent need for epidemiologic studies of vectorborne diseases in areas of endemicity to improve our ability to accurately differentiate febrile infectious diseases with atypical signs and symptoms during the initial stages so they can be promptly treated.…”
Section: Dispatchesmentioning
confidence: 99%
See 1 more Smart Citation
“…SFTSV infections are endemic in eastern Asia, and retrospective studies have confirmed its presence in China in 1996 (6), South Korea in 2000 7, Japan in 2005 (8), and Vietnam in 2017 (9). In addition, mixed infection with SFTSV and O. tsutsugamushi has been detected in patients in South Korea, where both pathogens are endemic (7,10). These results further emphasize the urgent need for epidemiologic studies of vectorborne diseases in areas of endemicity to improve our ability to accurately differentiate febrile infectious diseases with atypical signs and symptoms during the initial stages so they can be promptly treated.…”
Section: Dispatchesmentioning
confidence: 99%
“…We compared results of phylogenetic analysis of the 9 tsa56 gene sequences with sequences from 17 protogenotypes (1), which revealed >5 genotypes, including Karp_A (4/9, 44.4%), Karp_B (1/9, 11.1%), Kato_B (2/9, 22.2%), Gilliam (1/9, 11.1%), and JG_C (1/9, 11.1%) ( Figure 2). Finally, we used reverse transcription PCR analysis to investigate possible SFTSV infection in the patients (7,9,13). Among 152 patients' serum samples, 5 (3.3%) were positive for the partial small (S) segment of the SFTSV RNA genome, indicating SFTSV infection.…”
Section: Genotypic Heterogeneity Of Orientia Tsutsugamushi In Scrub Tmentioning
confidence: 99%
“…In addition, these two diseases share common clinical features, such as fever, nausea, vomiting, diarrhea, headache, and muscle pain, as well as overlapping disease regions. Furthermore, many cases of coinfection with SFTSV and O. tsutsugamushi have been reported [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with more and more reports of co-infection of SFTSV and O . tsutsugamushi [ 12 , 29 31 ], as well as, SFTS and scrub typhus had overlapped epidemic seasons [ 30 , 32 , 33 ], it is suspected that chiggers might play a role in the transmission of SFTSV. In addition, a Chinese literature reported that SFTSV was detected by PCR in mites ( Laelaps echidninus , family Laelapidae and L .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with more and more reports of co-infection of SFTSV and O. tsutsugamushi [12,[29][30][31], as well as, SFTS and scrub typhus had overlapped epidemic seasons [30,32,33], it is suspected that chiggers might play a role in the transmission of SFTSV. In addition, a Chinese literature reported that SFTSV was detected by PCR in mites (Laelaps echidninus, family Laelapidae and L. scutellare, family Trombiculidae) collected from rodents and goats in Jiangsu Province [34], which further deepened the suspicion of chigger's role in transmission of SFTSV.…”
Section: Introductionmentioning
confidence: 99%